Pengembangan Model Pembelajaran PJBL Berbasis STEAM Untuk Meningkatkan Kemampuan Fisik Motorik Anak TK ABA Masjid Raya Pagaralam - Seftiani, Yulia; Zubaedi, Zubaedi; Alimni, Alimni (UIN Fatmawati Sukarno Bengkulu, 2025)
This study aims to develop a valid STEAM-based PJBL teaching module to improve children's Physical Motor skills at ABA Kindergarten, Pagaralam Grand Mosque. This type of research is Research and Development (R&D) using the ADDIE development model. The ADDIE development model has 5 stages, namely analysis, design, development, implementation, and evaluation. The research subjects were 16 children. The instruments used were expert validation sheets (material experts, language experts, media experts, and practitioner experts), teacher response questionnaires, pretests, and posttests. The results of the study showed that validation by validators from 4 expert teams, namely material experts with a percentage of 98.2%, language experts with a percentage of 92%, media experts with a percentage of 96.7%, and practitioner experts with a percentage of 96% in the very valid category. The results of the practicality assessment sheet for teacher responses to the developed teaching materials had an average score of 90% with a very practical category. The pretest score was 1.6, with the assessment criteria beginning to develop (MB) at 40.8%, and the posttest score was 3.3, with the criteria for very well developed (BSB) at 80%. This indicates that the STEAM-based PJBL learning module is effective for children.